Molecular comparison and evolutionary analyses of VP1 nucleotide sequences of new African human enterovirus 71 isolates reveal a wide genetic diversity. - Maël Bessaud; Richter Razafindratsimandresy; Antoine Nougairède; Marie-Line Joffret; Jagadish M Deshpande; Audrey Dubot-Pérès; Jean-Michel Héraud; Xavier de Lamballerie; Francis Delpeyroux; Jean-Luc Bailly (PLoS ONE)
Most circulating strains of Human enterovirus 71 (EV-A71) have been classified primarily into three genogroups (A to C) on the basis of genetic divergence between the 1D gene, which encodes the VP1 capsid protein. The aim of the present study was to provide further insights into the diversity of the EV-A71 genogroups following the recent description of highly divergent isolates, in particular those from African countries, including Madagascar. We classified recent EV-A71 isolates by a large comparison of 3,346 VP1 nucleotidic sequences collected from GenBank. Analysis of genetic distances and phylogenetic investigations indicated that some recently-reported isolates did not fall into the genogroups A-C and clustered into three additional genogroups, including one Indian genogroup (genogroup D) and 2 African ones (E and F). Our Bayesian phylogenetic analysis provided consistent data showing that the genogroup D isolates share a recent common ancestor with the members of genogroup E, while the isolates of genogroup F evolved from a recent common ancestor shared with the members of the genogroup B. Our results reveal the wide diversity that exists among EV-A71 isolates and suggest that the number of circulating genogroups is probably underestimated, particularly in developing countries where EV-A71 epidemiology has been poorly studied.